Análise da concordância do padrão facial em uma população amazônica - GONÇALVES, Marcelle Amanda Sena (2019)
Introdution: One of the greatest orthodontic challenges is the diagnosis, through which the treatment plan is performed. Therefore, not to be used as a result of incorrect planning and consequently a dubious prognosis. Aim: The objective of this study was to evaluate the agreement between the subjective analysis of face height of individuals with balanced and unbalanced faces between two groups of assessors, trained orthodontists and students of Specialization Courses Material and Methods: 25 right profile photographs, 25 smiley front photos and 25 smileless front photos, corresponding to 25 adults equally distributed between Pattern I, Pattern II, Pattern III, Pattern Short Face and Pattern Long Face. Photos and exams were excluded from growing individuals and patients with craniofacial syndrome. The photos were randomly organized in a Power Point presentation, with 3 images on each slide, generating a file of 25 slides. The sample of group G1 is composed of 25 orthodontists and the group G2 by 25 students of Specialized Courses in orthodontics, each evaluator received a printed album containing a presentation with 25 slides, a TCLE and a guideline for conducting the research. The evaluators had a period of one month to submit the form with the answers. Results: The result obtained with the Kappa weighted statistical test was k = 0,0018, resulting in a poor agreement between the groups of evaluators. Conclusion: The images with the highest level of agreement were those classified as Pattern I. The G1 group presented greater agreement and correct numbers among them in relation to the components of the G2 group.